Design and Trial of Probing Prompting-Based Electronic Learner Worksheet (E-LKPD) on Chemical Bonding Material - Neti Afrianis; Nurhaliza Gustin (Journal of Natural Science and Integration, 2025)
ABSTRACTThe rapid development of digital technology in education necessitates innovative learning media that actively engage students. A preliminary study conducted at SMA Negeri 12 Pekanbaru indicated that chemistry instruction predominantly relies on printed materials and PowerPoint presentations, which contributes to low levels of student participation and understanding. This study aims to design and evaluate the validity and practicality of a Probing Prompting-based Electronic Learner Worksheet (E-LKPD) focused on chemical bonding, as well as to examine its potential impact on students’ learning engagement. Employing a Research and Development (R&D) approach following the Borg and Gall model, the study was limited to five stages: data collection, planning, development, initial field trials, and product revision. Participants included two expert validators, two chemistry teachers, and twelve students from class X MIPA 6. Data were analyzed descriptively to determine the percentages of validity and practicality. Validation by material and media experts yielded scores of 90% and 88.63%, respectively, indicating a very high level of validity. Practicality assessments by teachers and students resulted in scores of 86.25% and 84.89%, respectively, confirming that the E-LKPD is highly practical. The novelty of this research lies in the integration of the Probing Prompting learning model with a digital worksheet platform (Liveworksheet), enhancing interactivity and inquiry-based learning in chemistry. The developed E-LKPD provides an innovative medium for teachers to improve students’ conceptual understanding and foster self-directed learning in the digital era.Keywords: electronic learner worksheet (E-LKPD), probing prompting, chemical bonding.